Body in the forbidden city - Liu, Peng (Curtin University, 2015)
This research offers an investigation into Chinese/Confucian bodies through exegetical writing using analytical discourse and creative practice in the form of painting. It reflects on diverse perspectives about the body in Chinese society during different historical periods. The space of the Forbidden City, Beijing, is an ideal site for analysing understandings of the Chinese body, as the space itself, such as its layout, designs and regulations, are all inscribed with Confucian values and cultural meanings.